The Relationship between Lean Management Practices and Environmental Performance among Manufacturing Companies in Selangor - Mohd Zulkepli, Ainaa’ Elisya; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2026)
This research paper discussed the relationship between lean management and environmental performance in manufacturing companies in Selangor, where environmental performance is a significant factor in contributing to sustainable manufacturing by enhancing energy efficiency, waste, and regulatory compliance. Lean dimensions like Just-in-Time (JIT), Total Productive Maintenance (TPM), Kaizen, and waste management are generally considered to have the ability to increase the efficiency of resources and improve environmental impact, but research that combines lean management and environmental sustainability is still limited in developing nations. A quantitative research design was utilized to collect data via a structured questionnaire on 377 manufacturing companies in Selangor and analyzed using descriptive and correlation analysis. According to the findings, lean management practices and environmental performance is highly implemented, especially in waste minimization, continuous improvement, energy efficiency, and environmental regulations, owing to the difficulties being presented by high implementation cost due to the use of early-stage technologies and their low implementation rates within the local manufacturing industry. Nonetheless, correlation analysis indicated that lean management practices had a weak and statistically insignificant correlation with the environmental performance (p = 0.720), making it clear that lean management practices do not necessarily lead to better environmental performance unless they are explicitly combined with environmental management practices. In general, the paper underscores the need to embrace integrated lean- green processes to contribute to sustainable manufacturing growth in Selangor and Malaysia.